Utilization of distiller's grains for energy conservation and emissions reduction: A comprehensive investigation on pyrolysis kinetics and air-steam gasification performances - Minwei Liu; Peng Wang; Jincan Zeng; Qin Wang; Xi Liu; Guori Huang; Rongfeng Deng; Jianbiao Chen (Case Studies in Thermal Engineering)
Distiller's grains (DGs) is the by-product during liquor brewing, can be utilized as a renewable fuel by pyrolysis and gasification techniques, promoting energy conservation and emissions reduction. The pyrolysis kinetics and air-steam gasification performances were examined through thermogravimetric analysis (TGA) and fixed-bed reactor experiments. The TGA results indicated that, the DGs pyrolysis roughly occurred at 140.0–400.0 °C, and two splitting peaks at about 310.0 °C and 350.0 °C, corresponded to the cracking of cellulose and lignin, respectively. The second and third pyrolysis stages separately had the activation energies of 188.0 and 148.1 kJ/mol, and could be severally described by (1-x)2 and (1-x)3.5. Air-steam gasification experiments of DGs were conducted to investigate the impacts of gasifying temperature, air volume flow, and steam flow on gas compositions and yields, lower calorific value of syngas (Qgas), efficiencies of carbon conversion and gasification (ηC and ηG). All performance parameters first grew and then reduced with temperature rising, and the highest values of Qgas, ηC and ηG all reached at 750 °C. The equivalence ratio (ER) of 0.4 and steam-to-DGs ratio of 0.5 were suggested for DGs gasification. The results of this study could provide useful information for the energy utilization of distiller's grains through pyrolysis and gasification.